Structural transformation as determinant of growth in the best performing sub-Saharan African states - Katarzyna Andrzejczak (Institute of Economic Research (IER), 2017)
Research background: Economic development in sub-Saharan Africa is of para-mount importance, yet it escapes most of the attempts to understand it better in the economic discourse and it remains a sensitive issue in politics, contradicting stake holders on national and international levels. The region still lags behind oth-ers in terms of technological advancement and economic development. It grew significantly in the precedent decade, but the extent of growth has not sufficiently translated to its development. Determining strategies for sub-Saharan Africa is a scientific challenge, which requires more attention. In the globalized, interconnect-ed reality, solving problems of the South is in the best interest of the North. Purpose of the article: The aim of this research is to analyse structural changes as factors of economic development in the best performing sub-Saharan African countries on the grounds of new structural economics in order to provide policy implications. Methodology/methods: Namibia, Botswana, South Africa and Gabon were se-lected as best performing economies in the region. Based on the literature review and the analysis of descriptive statistics, profiles of sample countries were set. This in turn allowed to determine potential explanatory variables for OLS model of economic development. In the model, factors relating to labour productivity, tech-nology and structural change were included. The data was sourced from WDI database, Gretl software was used for computations. Findings & Value added: This paper contributes to the literature by attempting to explain structural changes in the process of economic development in the sub-Saharan region on the sample of best performing states. New structural economics concept was applied to understand the problem of. Based on the results, policy implications were proposed with respect to technology promotion, natural re-sources management, and quality of institutions. The research was limited by data availability and reliability.
Keywords: O1; O3; O4; 330; economic development; sub-Saharan Africa; technology development; new structural economics